Crystal structure of luliconazole - Anna Ben; Lilianna Chęcińska (Acta Crystallographica Section E: Crystallographic Communications)
The crystal structure of luliconazole {LCZ; C14H9Cl2N3S2; systematic name: (E)-[(4R)-4-(2,4-dichlorophenyl)-1,3-dithiolan-2-ylidene](1H-imidazol-1-yl)acetonitrile} is reported. In the molecule of the title compound, the dithiolane ring adopts an envelope conformation, while the dichlorophenyl ring exhibits disorder. In the crystal packing of luliconazole, only two intermolecular C–H...N hydrogen bonds are observed. Hirshfeld surface analysis reveals that the most dominant contacts are H...N/N...H, H...Cl/Cl...H, H...H and C...H/H...C.